A Validity Argument in Support of the Use of College Admissions Test Scores for Federal Accountability. Issue 4 (1st October 2019) - Camara, Wayne J.; Mattern, Krista; Croft, Michelle; Vispoel, Sara; Nichols, Paul
Abstract: In 2018, 26 states administered a college admissions test to all public school juniors. Nearly half of those states proposed to use those scores as their academic achievement indicators for federal accountability under the Every Student Succeeds Act (ESSA); many others are planning to use those scores for other accountability purposes. Accountability encompasses a number of different uses and subsumes a variety of claims. For states proposing to use summative tests for accountability, a validity argument needs to be developed, which entails delineating each specific use of test scores associated with accountability, identifying appropriate evidence, and offering a rebuttal to counterclaims. The aim of this article is to support states in developing a validity argument for use of college admission test scores for accountability by identifying claims that are applicable across states, along with summarizing existing evidence as it relates to each of these claims. As outlined by The Standards for Educational and Psychological Testing, multiple sources of evidence are used to address each claim. A series of threats to the validity argument, including weaker alignment with content standards and potential influences in narrowing teaching, are reviewed. Finally, the article contrasts validity evidence, primarily from research on the ACT, with regulatory requirements from ESSA. The Standards and guidance addressing the use of a "nationally recognized high school academic assessment" (Elementary and Secondary Education Act (ESEA), Negotiated Rulemaking Committee; Department of Education) are the primary sources for the organization of validity evidence.